Multi-level considerations for optimal implementation of long-acting injectable antiretroviral therapy to treat people living with HIV: perspectives of health care providers participating in phase 3 trials - Andrea Mantsios; Miranda Murray; Tahilin S. Karver; Wendy Davis; Noya Galai; Princy Kumar; Susan Swindells; U. Fritz Bredeek; Rafael Rubio García; Antonio Antela; Santiago Cenoz Gomis; Miguel Pascual Bernáldez; et al. (BMC, 2021)
Abstract Background Long-acting injectable antiretroviral therapy (LA ART) has been shown to be non-inferior to daily oral ART, with high patient satisfaction and preference to oral standard of care in research to date, and has recently been approved for use in the United States and Europe. This study examined the perspectives of health care providers participating in LA ART clinical trials on potential barriers and solutions to LA ART roll-out into real world settings. Methods This analysis draws on two data sources: (1) open-ended questions embedded in a structured online survey of 329 health care providers participating in the ATLAS-2 M trial across 13 countries; and (2) in-depth interviews with 14 providers participating in FLAIR/ ATLAS/ATLAS-2 M trials in the United States and Spain. Both assessments explored provider views and clinic dynamics related to the introduction of LA ART and were analyzed using thematic content analysis. The Consolidated Framework for Implementation Research (CFIR) was drawn on as the conceptual framework underpinning development of a model depicting study findings. Results Barriers and proposed solutions to LA ART implementation were identified at the individual, clinic and health system levels. Provider perceptions of patient level barriers included challenges with adhering to frequent injection appointments and injection tolerability. Proposed solutions included patient education, having designated staff for clinic visit retention, and clinic flexibility with appointment scheduling. The main provider concern was identifying appropriate candidates for LA ART; proposed solutions focused on patient provider communication and decision making. Clinic level barriers included the need for additional skilled individuals to administer injections, shifts in workflow as demand increases and the logistics of cold-chain storage. Proposed solutions included staff hiring and training, strategic planning around workflow and logistics, and the possibility of offering injections in other settings, including the home. Health system level barriers included cost and approvals from national regulatory bodies. Potential solutions included governments subsidizing treatment, ensuring cost is competitive with oral ART, and offering co-pay assistance. Conclusions Results suggest the importance of multi-level support systems to optimize patient-provider communication and treatment decision-making; clinic staffing, workflow, logistics protocols and infrastructure; and cost-related factors within a given health system.